Studies on pyrolysis of rice husk using Taguchi's l9 Orthogonal Array - Dang, K.V. (Trans Tech Publications Ltd, 2014)
Conversion and yield of liquid product using semi-batch reactor are investigated. Selected reaction parameters were optimized, using Taguchi L9 Orthogonal Array method for the design of experiments, to yield the highest liquid product. The investigated parameters include nitrogen flow rate, sample particle size, temperature and heating rate. The effects and significance of each parameter was studied and verified through repetitive experiments. Optimum conditions for the reaction were established. Optimum conditions for pyrolysis process were at 100 ml/min of nitrogen flow rate, temperature at 500 â, 20 â/min of heating rate and 250Î¼m - 500Î¼m of particle size with liquid yield of 35.48wt. Â© 2014 Trans Tech Publications, Switzerland.